A Project feasibility study on the continuous casting of copper in the Philippines - Ragasa, Catherine G. (College of Engineering, 1995)
Continuous casting of copper rods (CCR) is a relatively new process in the Philippines though it has been widely adapted in Europe and America. In Asia, Korea and Japan are the primary producers of copper rods. The Philippine importation of continuously cast rods is steadily growing and its major market is the wire and cable industry which has started to use CCR after realizing its advantages compared to the traditional copper rods. The major suppliers of the Philippines are Australia, Japan and Taiwan. There is a 2-3% projected growth rate in the importation of other ASEAN countries which increased the demand of CCR. Copper cathode, the basic raw material of copper rod has been manufactured in the Philippines by the Philippine Associated Smelting and Refining Corporation (PASAR). It produces about 172,500 metric tons per year and can sell 10-15% of its products to local customers. The supply of cathode available is enough to supply the needs of a CCR plant in the Philippines. Producing copper rods locally would mean savings for current importers since they will be able to save about 0.55 dollars per kg on taxes, freight costs and other duties. Importation of CCR to ASEAN countries will prove beneficial to the country through dollar inflows. Taking into account the supply and demand patters, the target demand for continuously cast copper rods is determined to be 24,000 tons annually of which 50% is to be sold to local buyers and the remaining 50% is for export to ASEAN countries. The basic difference of CCR and the traditional process is that continuous casting eliminates the process of cooling cast bars then reheating them to room temperature. This process results to reduced materials handling and shorter production time. It also forms more uniform rods and requires less welding when producing wires of longer lengths. The primary equipments used in CCR production are: melting furnace, holding furnace, withdrawal machine, coilers and heavy drawing machine. After evaluating two alternative machines, the horizontal continuous casting equipment was chosen at a price of P 151,675,000. Other equipment needed are platform scale, laboratory equipment 1250 kVA generator, overhead crane, forklifts and 18 ton trucks. The site of the plant is near the Manila ports and its customers are primarily located in Metro Manila. The basic raw material, copper cathode, will be supplied by Philippine Associated Smelting and Refining Corporation (PASAR) with a 3% transportation cost. The plant will be employing a total of 51 workers for its24 hour, 365 day operation and will be spending P 4,722,600 per year for salaries and benefits. The total initial investment for fixed assets, including land, construction of building and warehouse, purchase of equipment, machineries, transportation facilities sum up to P 163,677,300. Pre-production expenses which includes registration fees, legal fees, promotion, commissioning and training amount to P 850,000. Considering all the production and administrative expenses for a year of operation, it will cost P 1,301,860,000 or the cost of producing rods is P 54,244.356 per ton. The total project cost, including fixed investments, start-up costs and 2 months of working capital, will be equal to P 303,470,980. Seventy percent of the project cost will be provided by the Development Bank of the Philippines through its Industrial Lending Programs and the remaining 30% will be equity financing. Financial statements have been prepared for six years assuming constant production and sales. Net income is about P 280M per year, cash balance ending increases yearly at an average rate of 39% and the company assets are projected to increase by 22% annually. The test of Liquidity conducted shows that asset to liability ratio of the company is high meaning there is less debt pressure and debtors can expect prompt payments. In terms of operational efficiency, the company depends less on its equities and uses more of its profits. The payback period, which shows the time of recovery of investments, is 1.8 years. This short payback period signifies that investing in the project is profitable and initial investments can be easily recovered. Taking into account the results of the market, technical, financial and socio-profitability studies, it can be concluded that the project is FEASIBLE.